Vagal schwannoma in parapharyngeal space -anatomical perspective - Mishra, Suniti Raj; Singh, Shailendra; Gautam, Harendra Kumar; Singh, Ashutosh; Pantola, Chayanika; Kumar, Sushobhana; Singh, Rahul; Passey, Jigyasa (Asian Journal of Medical Sciences, 2015)
A rare case of Schwannoma of Vagus nerve in Parapharyngeal Space was admitted in Otolaryngology department of GSVM Medical College, Kanpur, Uttar Pradesh, India. Schwannoma is a rare tumor in the Parapharyngeal Space. The patient was a 32 yr old male with chief complaints of difficulty in swallowing and swelling in the neck since last 4 years. On examination there was a firm swelling on right side of neck and uvula was deviated towards Left Side. On CT & MRI examination a heterogenous mass was seen in Parapharyngeal space. The case was diagnosed as a case of vagal schwannoma in parapharyngeal space. The tumor was surgically excised. Histopathological Examination revealed the Tumor as Schwannoma. Asian Journal of Medical Sciences Vol.7(2) 2015 100-103